2014
DOI: 10.1134/s1023193514100061
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the solution flow rate on the final mass of metals deposited into a porous electrode at individual and joint deposition. Frontal delivery of solution

Abstract: Calculations in terms of the model of metal codeposition into a porous electrode (PE) and exper imental measurements are used for studying how the flow rate m v and the volume of circulating solution at its frontal delivery affect the final mass of the cathodic deposit and its spatial distribution. For both individual and joint deposition of metals, the correlation between the final mass of the cathodic deposit m f and the uni formity of its distribution in PE is demonstrated: the more uniform the deposit dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In our previous study [1], we analyzed the effect of the flow rate on the final mass and spatial distribution of two metals at the frontal delivery of solution into a porous electrode (PE). It was shown that when the profiles of potential Е(х) and metal ion concentration с(х) inside PE change in one direction, which is typi cal of both this mode of delivery and an equipotential PE, the dependences of the final metal deposit mass m f on the volume solution flow rate m v represent non monotonic curves with flat maximums at relatively high m v (of the order of magnitude of 1-2 cm 3 /s) for both individual deposition and codeposition.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study [1], we analyzed the effect of the flow rate on the final mass and spatial distribution of two metals at the frontal delivery of solution into a porous electrode (PE). It was shown that when the profiles of potential Е(х) and metal ion concentration с(х) inside PE change in one direction, which is typi cal of both this mode of delivery and an equipotential PE, the dependences of the final metal deposit mass m f on the volume solution flow rate m v represent non monotonic curves with flat maximums at relatively high m v (of the order of magnitude of 1-2 cm 3 /s) for both individual deposition and codeposition.…”
Section: Introductionmentioning
confidence: 99%